Factors Related with the Incidence of Dengue Hemorrhagic Fever at Tobelo Regional General Hospital - Olivia Asih Blandina; Julian Debora Talasi (BIOSAINSTEK, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by infection with the Dengue virus. DHF is an acute disease with clinical manifestations of bleeding that causes shock that leads to death. DHF can attack any age group, from children under 15 years of age to adults aged 15 years and over. Symptoms of DHF are fever for 2-7 days with a temperature of 3.90C, headache, pain in the back and epigastrium. Identifying factors related to the occurrence of DHF in Rulmalh Salkit Ulmulm Daleralh Tobelo. This study is a descriptive analytical study with a quantitative design. The sample obtained was 63 respondents. The variables studied included age, knowledge, 3Mplus mosquito nest eradication activities, and the habit of hanging clothes. The study found no significant relationship between age factors, knowledge, mosquito nest eradication & 3Mplus activities, clothes hanging habits with the incidence of Dengue Fever. knowledge (p = 0.264), mosquito nest eradication & 3Mplus (p = 0.723), clothes hanging habits (p = 0.123). There is no significant relationship with all variables because the p value is >0.05. Most of the ages that cause Dengue Fever incidents at the Tobelo Regional General Hospital are <25 years. Most of the respondents at the Tobelo Regional General Hospital have good knowledge with a percentage of (100%). Most of the respondents at the Tobelo Regional General Hospital do not carry out mosquito nest eradication & 3Mplus activities properly 51%. Most of the respondents have bad clothes hanging habits with a percentage of (95%).